Growth patterns of small scale plants in manufacturing industries: A cross-country analysis - Ranadev Banerji (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1977)
An important issue that confronts small sector development policy in manufacturing is the question of whether small-scale plants are in the long-run viable or must they disappear in the development process. This question is important because answers to it may indicate whether small-scale plants are worthwhile developing in the first place and, if they are, which specific industries appear most appropriate for the purpose. Clearly, central to the issues raised are questions of economies of scale and production function in manufacturing. In planning investments the method of mathematical programming has proved to be quite useful in coping with them. In this paper an attempt is made to apply the patterns approach to development as a method of dealing with the question raised in a general way. Briefly, this approach involves estimating by means-of econometric methods the observed long-term quantitative relationship between a sector's relative importance in the economy and a set of variables systematically affecting the sector, in order to be able to indicate its possible development path over time. While the major concern of the patterns approach to development to date has been with structural composition of industries, this paper looks at intercountry differences in the size structure of plants within individual industries. The principal concern of this paper is with the scale effects of economic development and market size on small-scale plants. Assume that at any point of time the same choices of techniques are open to all producers in a given industry in all countries and that these choices are mapped by a production function which is linearly homogeneous. Furthermore assume, to begin with, that the relative factor prices between labour and capital (the two primary factors of production) are the same for all producers in all countries. Under these simplifying assumptions, one sense in which the size of plant in a given industry can vary from country to country is when the size of market is different from one country to another. All other things being equal, the size of plant and that of the market will be positively associated, with one another.
Keywords: 330